Quantitative analysis of the influence of voids and delaminations on acoustic attenuation in CFRP composites by the laser-ultrasonic spectroscopy method - Karabutov, A.A.; Podymova, N.B. (Composites. Part B, Engineering, 2014)
The aim of the present work is to develop the ultrasonic spectroscopy method using laser thermoelastic generation and piezoelectric detection of broadband acoustic pulses for quantitative evaluation of the influence on the ultrasonic attenuation coefficient of microscopic dispersed voids and interply delaminations in CFRP laminates. The specimens under study have different entire porosity values up to 10% determined by the X-ray computer tomography. The ultrasonic attenuation resonance is observed in all specimens governed by their periodic layered structure. The absolute maximum and the frequency bandwidth of the resonance peak depend on the total porosity level formed by the predominant type of imperfections, either of only microscopic spheroidal voids entrapped in the epoxy layers or of additional extended interply delaminations. The derived empirical relations between these parameters and the total porosity level can be used for rapid nondestructive evaluation of the structure of CFRP composite laminates subject to different manufacturing conditions.